A (re)construção de um Projeto Político-Pedagógico-Participativo na Educação Básica: aspectos da pesquisa dialógica e participativa - Martins, Elisa Pires (2024)
This study has as its main theme the process of discussion and (re)building the political-pedagogical-participative project (PPP-P) in a Primary School in the west zone of the city of São Paulo. The research was developed between the research group “Educational Practices and Psychoeducational Attention on School, Family and Community” (ECOFAM) and the school. The project came from a complaint from the pedagogical coordination and the research question was defined collectively: “How to (re)build a participative and dialogical political-pedagogical project?”. The main objective of the research was to understand the process of preparing the political-pedagogical project, which took place in a collaborative and participative manner between the aforementioned research group, the school and the university. The process was carried out in the territory with the participation of families and pedagogical coordinators. The research method was dialogical and participative and the research is inspired by phenomenological